Remembering the Leaders of China - Fu, Mingchen; Xue, Yan; DeSoto, K. Andrew; Yuan, Ti-Fei (Frontiers in Psychology, 2016)
In two studies, we examined Chinese students’ memory for the names of the leaders of China. In Study 1, subjects were cued with the names of periods from China’s history. Subjects listed as many leaders as possible from each period and put them in the correct ordinal position when they could (see Roediger & DeSoto, 2014). Results showed that within each period, a primacy effect and sometimes a recency effect emerged. Moreover, the average recall probability for leaders within a specific period was a function of the ordinal position of the period. In Study 2, we asked another group of subjects to identify the sources through which they were able to recall each leader. We found that most subjects remembered leaders thanks to class and coursework. We also found a relation between a leader’s recall probability and the amount of information available on that leader on the Internet. Our findings further imply that the serial position function captures the form of collective memory.